Pembelajaran Multikeaksaraan: (Suatu Pendekatan Optimalisasi Pengelolaan Pembelajaran) - abd Hamid Isa (Jurnal AKRAB, 2019)
Multiliteracy Education as one of Literacy Education parts is developed in terms of eradicating illiteracy of adults and as community empowerment based on their own potential. The literacy education program is developed in basic and advanced literacy services. The advanced literacy education comprised independent business literacy education and multiliteracy education. The multiliteracy education aims to develop the competence of community after having basic literacy education, and it emphasizes the improvement of literacy diversity in all aspects of life. The research was conducted due to the presence of a problem regarding workable effort to optimize learning management to advance the learning quality of students. The research objective was to find out the objective condition of learning management and to depict efforts of optimizing learning quality which could affect competence achievement of attitude, knowledge, and skill of students. The research site was in Tabongo Sub-district, Gorontalo District, Gorontalo Province. It was qualitative descriptive research with a phenomenological approach. The data sources of research were teachers and students. The data were collected through techniques of observation, questionnaire, interview, and documentation. The technique of data analysis used data reduction, data display, and conclusion drawing. The findings of research revealed that the objective condition of learning management was not performed optimally yet which affected the learning productivity. In addition, there was a necessary to develop teachers’ (tutor) competence well to be qualified and a relatively adequate facility for the implementation. To optimize the multiliteracy learning, it was necessary to develop learning structure which referring to strengthening ability, use of multiple intelligence, and using varied ways that have been trained in a study group to understand reality outside or at work environment.